SOLID FUEL FROM EMPTY FRUIT BUNCH FIBER AND WASTE PAPERS PART 5: CRACK TEST FOR TRANSPORTATION AND STORAGE PURPOSE - YAAKOB, MOHD YUHAZRI; HASOLOAN, HAERY IAN PIETER; YAHAYA , SAIFUDIN HAFIZ; SAID, MD RADZAI (Global Engineers and Technologists Review, 2012)
This research discussed on the results obtained for each sample that have been conducted to the solid fuel briquettes made of empty fruit bunch fiber and waste papers from view of mechanical performance which is crack test for transportation and storage purpose. This solid fuel prepared by manual compression technique and tested using drop test equipment. This analysis important to know the capability of the solid fuel to sustained/maintained the physical shape after transportation and storage activities. Experimental work shows that most samples of solid fuel have good performance for the test.